A novel EZH2/NXPH4/CDKN2A axis is involved in regulating the proliferation and migration of non-small cell lung cancer cells. Issue 12 (17th December 2021) - Yang, Zeng; Wei, Bo; Qiao, Anbang; Yang, Popo; Chen, Wenhui; Zhen, Dezhi; Qiu, Xiaojian
ABSTRACT: NXPH4 is discovered to be a neuropeptide-like glycoprotein, belonging to the Neurexophilins (Nxphs) family. NXPH4 shares a similar domain structure with NXPH1, which, however, is poorly understood in terms of its function. Bioinformatics analysis and experimental verification in this study confirmed the abnormal high expression of NXPH4 in non-small cell lung cancer (NSCLC) tissues and cells. Knockdown of NXPH4 by siRNA can inhibit the proliferation and migration of cells, resulting in significant cell cycle arrest in S1 phase. Furthermore, in NSCLC cells, NXPH4 was regulated by transcriptional activation of enhancer of zeste homolog 2 (EZH2) in its upstream. While downstream, NXPH4 could interact with CDKN2A and downregulate its protein stability, thus participating in the cell cycle regulation through interacting with cyclinD-CDK4/6-pRB-E2F signaling pathway. To sum up, the present study reveals a regulatory pathway of EZH2/NXPH4/CDKN2A in NSCLC, providing possible reference for understanding the function of NXPH4 in tumors. Graphical Abstract: